Evaluation and management of acute upper airway obstruction. Issue 10 (October 2018) - Yiannakis, Constantina P.; Hilmi, Omar J.
Abstract: Upper airway obstruction can occur suddenly and result in a patient's rapid deterioration. In this article we provide a structured approach to identifying those patients with acute airway compromise and stratifying them according to clinical urgency. This includes ways of distinguishing both the level of obstruction and its severity, based on the clinical signs and symptoms, and the role and timing of investigations. We describe the key aspects of emergency management, including temporizing measures and airway adjuncts. Management of rare, but important, situations are discussed such as post-thyroidectomy haematoma, occlusion of tracheostomy and laryngectomy stomas and post-obstruction pulmonary oedema (POPE) is discussed. We describe the situation when an emergency surgical airway should be considered, along with our technique of performing one.